Analyzing The Use of Metaphors In The Lyrics of PinocchioP’s Songs - Aprena Fatih Almas; Dwi Puspitosari (Japanese Department Faculty of Cultural Science Universitas 17 Agustus 1945 Surabaya, 2026)
Metaphor is figure of speech that is often used in written and spoken works of art such as songs as a way of connecting two similar things without using comparative words. This study aims to examine the use of metaphors in PinocchioP's songs through Stephen Ullmann's four classifications of metaphors: anthropomorphic, abstraction, synesthetic, and Zoomorphic. This study uses qualitative descriptive approach with listening and note-taking technique on 27 songs contained in PinocchioP's BEST ALBUM 2009-2020 Kotobuki. It can be concluded that all four classifications of metaphors according to Ullmann's classification method appear in 26 of the 27 songs analyzed. There are seventy-one pieces of data from 26 songs in the album PinocchioP Best Album 2009-2020 Kotobuki. Abstraction metaphors appear most frequently in the lyrics of PinocchioP's songs with 39 pieces of data. Anthropomorphic and synesthetic metaphors appear 12 times respectively. Zoomorphic appeared last with eight instances. This shows that metaphors are one of the linguistic tools frequently used by PinocchioP. The meaning conveyed by each metaphor also depends on the context of the song lyrics and their relationship to the theme. Most of the themes raised are “relationships,” either with other people (Kimi mo Warui Hito de Yokatta, Yozurina) or with oneself (Slow Motion, Motivation ga Shindeiru) or even to Hatsune Miku herself (Aisarenakute mo Kimi ga Iru, 10-nengo no VOCALOID no Uta). The role of this theme supports the use of metaphors as a way for PinocchioP to give deep impression and impact in the lyrics of his songs.